2016
DOI: 10.1080/17476348.2016.1177461
|View full text |Cite
|
Sign up to set email alerts
|

Newer developments in idiopathic pulmonary fibrosis in the era of anti-fibrotic medications

Abstract: Idiopathic pulmonary fibrosis (IPF) is the most common interstitial lung disease with a fatal prognosis. Over the last decade, the concepts in pathobiology of pulmonary fibrosis have shifted from a model of chronic inflammation to dysregulated fibroproliferative repair in genetically predisposed patients. Although new breakthrough treatments are now available that slow the progression of the disease, several newer anti-inflammatory and anti-fibrotic drugs are under investigation. Patients with IPF often have coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 114 publications
0
6
0
1
Order By: Relevance
“…In agreement with other studies, our study showed that IPF is predominantly a disease of elderly people, and several important findings emerged from our study. IPF is associated with a poor prognosis, but survival is difficult to predict for individual patients [7,36].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other studies, our study showed that IPF is predominantly a disease of elderly people, and several important findings emerged from our study. IPF is associated with a poor prognosis, but survival is difficult to predict for individual patients [7,36].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Conventionally, the IPF clinical course can be categorized into three types based on the rate of the forced ventilation capacity (FVC) decline: slow deterioration (less than 10% decline in FVC over 6 months or no changes in the disease indicators for many months), intermittent deterioration with episodes of exacerbations and rapid deterioration (more than 10% decline in FVC for 6 months). 3,6,7 For the last type, before the era of antifibrotic medications, the life expectancy of patients did not usually exceed 2 years from the time of diagnosis. [6][7][8] Besides acute exacerbations, a poor prognosis might be suspected in patients with IPF with such predictors as low values of FVC and diffusing capacity of the lung for carbon monoxide (DLCO), old age, and a high rate of pulmonary function decline.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,7 For the last type, before the era of antifibrotic medications, the life expectancy of patients did not usually exceed 2 years from the time of diagnosis. [6][7][8] Besides acute exacerbations, a poor prognosis might be suspected in patients with IPF with such predictors as low values of FVC and diffusing capacity of the lung for carbon monoxide (DLCO), old age, and a high rate of pulmonary function decline. 3,9 The majority of clinical studies on the drug therapy of IPF did not evaluate the pretreatment functional reduction rate 10,11 ; therefore, it is difficult to judge its efficiency in patients with a fast lung function decline.…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter with an aerodynamic diameter of < 2.5 µm (PM2.5) is involved in the pathogenesis of various respiratory diseases because of the toxicity of these particles, which originate from various sources [1,2]. Harmful environmental factors can reportedly induce pulmonary brosis (PF) [3], which is associated with epithelial-mesenchymal transition (EMT) and extracellular matrix (ECM) [4,5]. As an important pathway of stromal cell production and excess ECM deposition, EMT can promote scar tissue formation in the lungs, eventually leading to the development of PF [6].…”
Section: Introductionmentioning
confidence: 99%